2020
DOI: 10.1109/access.2020.3036092
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Economic Dispatching Strategy of the Active Distribution Network Based on Comprehensive Typical Scenario Set

Abstract: The increasing penetration of renewable energy resources in the distribution network has posed great uncertainties and challenges for the system security operation. To model various uncertain factors like the wholesale market price and renewable energy generation in the active distribution network (ADN), a similarity measurement method considering the amplitude, volatility and variation trend is proposed. The Latin hypercube sampling method and Graph Pyramid clustering algorithm are adopted to obtain the compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…New stakeholders, such as generic power providers and consumers, are actively specifying power generating and use plans, participating in power grid dispatching, and reaping economic benefits as a consequence. Furthermore, by delegating the power grid's dispatching control authority over generalized power generation to each distributed generating operator for autonomous management, the enormous scale and complex control challenges of generalized power generation optimization may be handled [18][19][20]. On the other hand, each stakeholder has its own power generating and consumption plan as well as optimization objectives.…”
Section: Construction Of Multiobjective Coordinated Optimization Game Model For Generalized Power Active Distribution Networkmentioning
confidence: 99%
“…New stakeholders, such as generic power providers and consumers, are actively specifying power generating and use plans, participating in power grid dispatching, and reaping economic benefits as a consequence. Furthermore, by delegating the power grid's dispatching control authority over generalized power generation to each distributed generating operator for autonomous management, the enormous scale and complex control challenges of generalized power generation optimization may be handled [18][19][20]. On the other hand, each stakeholder has its own power generating and consumption plan as well as optimization objectives.…”
Section: Construction Of Multiobjective Coordinated Optimization Game Model For Generalized Power Active Distribution Networkmentioning
confidence: 99%
“…The LHS method is used in the proposed work due to two main advantages compared to the MCS [29]- [32]:…”
Section: A Latin Hypercube Sampling (Lhs) Methodmentioning
confidence: 99%
“…As a result, the original probability distribution of the uncertain parameters is fully maintained in the produced samples, and • Lower number of simulations and computations. The steps of the LHS method can be summarized as follows [32]:…”
Section: A Latin Hypercube Sampling (Lhs) Methodmentioning
confidence: 99%
“…However, limited by the model complexity and computational efficiency, the proposed VVC method may be incapable of handling a large distribution network with various DERs. Additionally, these scholars (Ma et al, 2021;Zhu et al, 2020) dissect the random fluctuation characteristics of PV plants via multi-scenario modeling, improving ADNs' efficiencies and economics. To reduce the PV curtailment and network loss, a non-dominated sorting genetic algorithm II (NSGA-II)-based voltage regulation method is proposed in (Ma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although the NSGA-II algorithm is easy to implement, it does not guarantee the global optimum in practical applications. The study reported in (Zhu et al, 2020) constructs a typical scenario set-based approach to address the stochastic economic dispatching, preestablishing charging and discharging schemes for controllable generation units, PV systems, wind farms, and ESSs. However, it suffers a heavy computational burden due to the need to consider many scenarios.…”
Section: Introductionmentioning
confidence: 99%